A Light-Inducible Split-dCas9 System for Inhibiting the Progression of Bladder Cancer Cells by Activating p53 and E-cadherin - Huang, Xinbo; Zhou, Qun; Wang, Mingxia; Cao, Congcong; Ma, Qian; Ye, Jing; Gui, Yaoting (Frontiers in Molecular Biosciences, 2021)
Optogenetic systems have been increasingly investigated in the field of biomedicine. Previous studies had found the inhibitory effect of the light-inducible genetic circuits on cancer cell growth. In our study, we applied an AND logic gates to the light-inducible genetic circuits to inhibit the cancer cells more specifically. The circuit would only be activated in the presence of both the human telomerase reverse transcriptase (hTERT) and the human uroplakin II (hUPII) promoter. The activated logic gate led to the expression of the CDH1 gene, which could inhibit the biological function of tumour cells. In addition, we split the dCas9 protein to reduce the size of the synthetic circuit compared to the full-length dCas9. This light-inducible system provides a potential therapeutic strategy for future bladder cancer.